2009
DOI: 10.1111/j.1442-200x.2008.02666.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical or radiologic measurements and 3‐D gait analysis in children with pes planus

Abstract: TMA was the factor most related to degree of calcaneal valgus measured on physical exam. Larger TCA contributed to decreased maximal external rotation and increased maximal internal rotation in gait cycle. Clinical or radiological methods, however, had very limited ability to predict gait deviance of pes planus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…It can also cause changes in the overall body position and increase the risk of back pain due to straining of muscles and effects on the pelvis, lower extremities, and even the spine in closed-chain exercise14,15,16 ) . However, there is little research focused on load-dependent muscular activity during walking with flatfoot subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It can also cause changes in the overall body position and increase the risk of back pain due to straining of muscles and effects on the pelvis, lower extremities, and even the spine in closed-chain exercise14,15,16 ) . However, there is little research focused on load-dependent muscular activity during walking with flatfoot subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in what concerns biomarkers to evaluate the risk of BIND, Bf is considered a more sensitive predictor (Ahlfors et al, 2009b; Lee et al, 2009) than either bilirubin–albumin molar ratio (UCB/HSA) or abnormal ABR maturation (Amin et al, 2001) and, in contrast to TSB levels, revealed to be associated with ABRs results (Ahlfors and Parker, 2008). In sum, Bf or TSB plus Bf, instead of TSB alone, are more rational indicators (Wennberg et al, 2006).…”
Section: Biomarkers and Predictors Of Bilirubin Neurotoxicitymentioning
confidence: 99%
“…Flatfoot results in problems on the static alignment of ankle and foot, as well as to the dynamic functional abnormality of the lower extremities [1]. Thus, proximal joints like the knee joints, hip joints, and the lower spine get affected due to the overloading of a medial longitudinal arch [2].…”
Section: Introductionmentioning
confidence: 99%